Luminescence sensing and photocatalytic activities of four Zn(ii)/Co(ii) coordination polymers based on a pyridinephenyl bifunctional ligand. Issue 6 (26th January 2021) - Xue, Yun-Shan; Zhang, Chen; Lv, Jun Qing; Chen, Ning-Ning; Wang, Jun; Chen, Xuan-Rong; Fan, Liming
Abstract : Four Zn(ii )/Co(ii ) CPs act as bifunctional materials in the detection of Fe(iii ) cation, Cr(vi ) anion, and nitrofuran antibiotics and removal of methylene blue in aqueous media. Abstract : Based on a novel pyridinephenyl bifunctional ligand of 5-(6-carboxypyridin-2-yl)benzene-1, 3-dicarboxylic acid (H3 L), four Zn(ii )/Co(ii ) coordination polymers (CPs), {[Zn(BIMB)(HL)]·H2 O} n (1 ), [Co(BIMB)(HL)(H2 O)] n (2 ), {[Zn2 (BIBP)2 (HL)2 ]·2H2 O} n (3 ), and {[Co3 (BIBP)3 (L)2 (H2 O)2 ]·5H2 O} n (4 ), have been constructed with the introduction of two length-suitable bis(imidazole) linkers (BIMB = 4, 4-bis(imidazol-1-ylmethyl)biphenyl; BIBP = 4, 4-bis(imidazol-1-yl)diphenyl). Structural analysis shows that CP 1 exhibits a 2D wave 4-c {4 4 ·6 2 } sql sheet, and CP 2 shows an interesting 2D + 2D → 2D interpenetrating structure with ABAB sql packing. CP 3 displays an unprecedented 3D (4, 4)-c {4 2 ·8 3 ·10}-tcj net. CP 4 presents a 2D (3, 4, 4)-c {6 2 ·7·8 2 ·10}{6 2 ·7 3 ·8}2 {6 3 }2 trilayer structure reported for the first time. Luminescence sensing exploration reflected two luminescent Zn(ii ) CPs possessing excellent performances in sensing Fe 3+ cation, Cr2 O7 2− /CrO4 2− anions, and NFT/NZF antibiotics in aqueous solution. Besides, the four obtained CPs also demonstrated outstanding potential as photocatalysts in the degradation of methylene blue (MB).